Charcot–Marie–Tooth disease due to MORC2 mutations in Spain. (18th July 2021) - Sivera, Rafael; Lupo, Vincenzo; Frasquet, Marina; Argente‐Escrig, Herminia; Alonso‐Pérez, Jorge; Díaz‐Manera, Jordi; Querol, Luis; del Mar García‐Romero, María; Ignacio Pascual, Samuel; García‐Sobrino, Tania; Paradas, Carmen; Francisco Vázquez‐Costa, Juan; et al.
Abstract: Background and purpose: MORC2 mutations have been described as a rare cause of axonal Charcot–Marie–Tooth disease (CMT2Z). The aim of this work was to determine the frequency and distribution of these mutations throughout Spain, to provide a comprehensive phenotypical description and, if possible, to establish a genotype–phenotype correlation. Methods: Retrospectively, data on patients diagnosed with CMT2Z in Spain were collected and clinical, electrophysiological and muscle imaging information were analysed. Results: Fifteen patients with CMT2Z were identified throughout Spain, seven of them belonging to a single kindred, whilst the rest were sporadic. The most common mutation was p.R252W, and four new mutations were identified. Eleven patients were categorized as having a scapuloperoneal phenotype, with asymmetric muscle weakness, early proximal upper limb involvement and frequent spontaneous muscular activity with distal sensory impairment and pes cavus, whilst two presented with a more classic length dependent sensory motor phenotype. This distinction was corroborated by the distribution of muscle fatty infiltration in muscle imaging. Two other patients were classified as having a neurodevelopmental phenotype consisting in congenital or early onset, delay in motor milestones, and global developmental delay in one of them. Nerve conduction studies revealed an unequivocally axonal neuropathy with frequent spontaneous activity, and serum creatine kinase levels were increased in 50% of the patients. Conclusions: MORC2 mutations are a rare cause of CMT in Spain, but in‐depth phenotyping reveals a recognizable phenotypic spectrum that will be clinically relevant for future identification of this disease. Abstract : MORC2 mutations are a rare cause of axonal Charcot–Marie–Tooth disease, and the clinical characteristics of 15 patients throughout Spain were analysed. Eleven patients with a scapuloperoneal phenotype, with asymmetric muscle weakness, early proximal upper limb involvement and frequent spontaneous muscular activity with distal sensory impairment and pes cavus were defined. There were also two patients with a classic length dependent sensory motor phenotype, and another two presented a neurodevelopmental phenotype with congenital or early onset, delay in motor milestones, and global developmental delay in one of them.